The effect of open-ended approach on enhancing mathematical understanding in vocational high school students - Rifai, Rusdian; Turmudi; Jarnawi Afgani Dahlan; Suhendra (KALAMATIKA Jurnal Pendidikan Matematika, 2025)
This study aims to evaluate the extent to which the open-ended approach affects the achievement of students' mathematical understanding ability in vocational high schools (SMK). The method used was a quasi-experiment with a pretest-posttest control group design, in which two groups of students (experimental group and control group) were compared based on test results before and after treatment. The research sample consisted of 72 students who were selected by intact group (based on the class that had been formed) to minimize disruption to teaching and learning activities at school. This sampling was done by considering the real conditions in the field so as not to disrupt the existing learning schedule and class structure. The research data was obtained through a description test consisting of three questions, with a maximum score of 12 for each question. Data analysis was conducted in two stages: first, a normality test to check data distribution, and second, a mean difference test using the Mann-Whitney U test because the data were not normally distributed. The results showed that the group of students taught with the open-ended approach had better mathematical understanding achievement than the group that received direct learning. This finding indicates that the open-ended approach is effective in promoting mathematical conceptual understanding through independent exploration.